A New Look at Radio and Television Teasers Using Conceptual Blending Theory - Hossein Razavian; Zahra Zare; Sahar Bahrami-Khorshid (مطالعات زبانی و بلاغی)
Conceptual blending theory was introduced to explain human creative ability in linking elements in different domains and to find a shared schema structure between them by Fauconnier and Turner (2000). This article tries to evaluate the adequacy of this theory in cognitive semantics in the field of advertising by examining samples of radio and television advertising teasers. For this purpose, 50 radio teasers and 50 television teasers were considered as samples of the use of innovative language, the conceptual combinations used are extracted and their conceptual blending networks are drawn. The results of the research show that the attention of the creators of advertisements emerging and emergent meaning as an aspect of creativity and its use as a means of attracting and encouraging the audience in these teasers is significant. The use of the blending in radio teasers is more than twice the size of the television teasers. The presence of the image in the television shows seems to take up a lot of meaning transfer and the linguistic language has a little chance of emergence in comparison to the visual text. It was also found that, among the types of blending, the application of the single-scope conceptual blending in the propaganda of both media is more common. There are a few mirror and double-scope blending, and none of the teasers surveyed included a simple blending. Considering the common use of metaphor in the language, believing in a metaphorical intellectual system and familiarity of the audience with this category, one can justify the more frequent single-scope blending.